2020
DOI: 10.3390/v12010064
|View full text |Cite
|
Sign up to set email alerts
|

A Chimeric Sudan Virus-Like Particle Vaccine Candidate Produced by a Recombinant Baculovirus System Induces Specific Immune Responses in Mice and Horses

Abstract: Viruses 2020, 12, 64 2 of 15 development against SUDV infection. Further, these horse anti-SUDV purified immunoglobulins lay a foundation for SUDV therapeutic drug research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The full-length gene-encoding structural matrix protein (VP40) and glycoprotein (GP) of Sudan virus were cloned in the pFastBacDual vector to yield recombinant bacmids, i.e., pFastBacDual-VP40-VP40 and pFastBacDual-GP-GP, respectively. The transfection and co-expression of recombinant bacmids in Sf-9 cells led to the production of immunogenic Sudan VLPs, which elicited the production of neutralizing antibodies and Th1 (T helper 1)- and Th2 (T helper 2)-type cytokine-secreting immune cells in mice models [ 124 ]. Wang et al [ 125 ] have demonstrated the potential of the baculovirus expression system in the elevated production of human papillomavirus (HPV) L1 capsid protein-based VLPs.…”
Section: Expression Platforms and Upstream Process Development Of Chi...mentioning
confidence: 99%
“…The full-length gene-encoding structural matrix protein (VP40) and glycoprotein (GP) of Sudan virus were cloned in the pFastBacDual vector to yield recombinant bacmids, i.e., pFastBacDual-VP40-VP40 and pFastBacDual-GP-GP, respectively. The transfection and co-expression of recombinant bacmids in Sf-9 cells led to the production of immunogenic Sudan VLPs, which elicited the production of neutralizing antibodies and Th1 (T helper 1)- and Th2 (T helper 2)-type cytokine-secreting immune cells in mice models [ 124 ]. Wang et al [ 125 ] have demonstrated the potential of the baculovirus expression system in the elevated production of human papillomavirus (HPV) L1 capsid protein-based VLPs.…”
Section: Expression Platforms and Upstream Process Development Of Chi...mentioning
confidence: 99%
“…Similarly, a trivalent vaccine against three types of zoonotic equine encephalitis virus was shown to produce complete protective immunity upon viral challenge in mice [48]. In 2019, an Ebola virus VLP vaccine candidate, with the matrix structural protein of the Sudan virus as the antigen, was produced in insect cells using the baculovirus expression system [49]. The VLP vaccine elicited B and T cell immune responses in vivo and is another example of the versatility of VLPs.…”
Section: Virus-like Particlesmentioning
confidence: 99%
“…These viruses have been known since 1911, and some members were successfully developed as biocontrol agent against agricultural and forest insect pests. Baculoviruses have also been developed as vectors for the expression of exogenous genes employed in a variety of sectors such as the pharmaceutical, medical and biotechnological [2,3]. Baculoviridae is divided into 4 genera, Alphabaculovirus (lepidopteran Nucleopolyhedroviruses), Betabaculovirus (lepidopteran Granuloviruses), Gammabaculovirus (hymenopteran NPVs) and Deltabaculovirus (dipteran NPVs) [4].…”
Section: Introductionmentioning
confidence: 99%